The Existence of God, in the Thinking of J. M. Méndez: In the Light of the Formalized Logic - Barraca Mairal, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This research explores the thought of J. M. Méndez about the ways of demonstrating the existence of God. Méndez is a current Spanish thinker who has written mainly about values, axiology, and logic. He rethinks this topic thanks to his reflection on the value of truth. Moreover, he follows a new path by resorting in this respect to logic and in particular to formalized logic. Our work develops a critical analysis of his argument.